Dampak Perubahan Indeks Saham Syariah Global Terhadap Indeks Saham Syariah Indonesia - Ritonga, Nailan; Muhammad Hafizh (Fakultas Ekonomi dan Bisnis Islam, 2025)
Global capital markets, including Islamic stock markets, are directly affected by the global uncertainty caused by the pandemic, high inflation, and economic turmoil in major countries. The purpose of this study is to evaluate the impact of changes in three global Islamic stock indices: Dow Jones Islamic Market Malaysia Titans 25 Index (DJIMY25), Dow Jones Islamic Market Japan Index (DJIJP), and Dow Jones Islamic Market Europe Index (DJIEU) over the period 2020-2024. The relationship between short- and long-term variables is evaluated through a quantitative approach with monthly time series data. In addition, the Vector Error Correction Model (VECM) method is also used. The results show that DJIMY25 has a significant influence on ISSI in both the short and long term, while DJIJP has a significant influence only in the short term. DJIEU, on the other hand, has no significant influence. Compared to other global indices, the influence of regional indices especially Malaysia on the ISSI is greater. This study not only provides theoretical contributions to the field of Islamic finance, but also provides practical advice for investors, regulators, and Islamic capital market players in Indonesia.